Economic Feasibility Analysis of Acquiring a Raw Material Carrier: A Case Study of the Libyan Iron and Steel Company (LISCO) (Journal of Academic Research, 2026)
The Libyan Iron and Steel Company (LISCO) faces significant operational and financial challenges due to its dependence on rented raw material carriers, which exposes the company to high and volatile transportation costs. This study investigates the economic feasibility of acquiring a 50,000-ton capacity raw material carrier to improve operational efficiency, reduce long-term expenditures, and enhance supply chain resilience. A quantitative economic analysis was conducted using key financial indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), Profitability Index (PI), Modified Internal Rate of Return (MIRR), Benefit-Cost Ratio (BCR), and Economic Value Added (EVA). Sensitivity analysis and Monte Carlo simulations were applied to evaluate the robustness of the investment under fluctuations in operational costs, fuel prices, utilization rates, and interest rates. Furthermore, a Real Options Analysis was performed to quantify additional strategic flexibility, encompassing options to expand, defer, or abandon the project. The findings reveal a positive NPV of $28.7 million, an IRR of 18.5%, a payback period of 5.1 years, and projected 20-year savings of $16 million compared to the current rental approach. Overall, the results confirm strong financial viability, resilience to market uncertainties, and strategic benefits, supporting the acquisition as a sound investment decision that enhances LISCO’s operational independence, cost efficiency, and long-term competitiveness.
Keywords: Economic Feasibility; Raw; Material Carrier; Net present value; Payback Period